Pelatihan Aksara Bali Sebagai Bentuk Akomodasi terhadap Kearifan Lokal - I Wayan Rudiarta; Gede Eka Puja Dyatmika (IAHN Gde Pudja Mataram, 2022)
Community service through Balinese script training for students of the Dharma Amertha Sari Pasraman has great meaning and significance for efforts to preserve non-material culture and local wisdom passed down by Balinese ancestors. Even though they have settled on the Lombok Island which is the original residence of the Sasak people, the responsibility for preserving this culture still lies with the younger generation. This Balinese script training activity is carried out in four stages, namely Define (defining/exploring problems), Design (designing the service concept to be carried out), Develop (developing material that will be used as material in training activities), and Dissemination (dissemination of information/material provided designed for students). The methods applied in the training activities are in the form of lecture methods, practice methods and discussion methods. Through the implementation of the training stages and methods that have been designed at the end of the training activities, students of the Dharma Amertha Sari Pasraman have a basic understanding for learning Balinese script in the future, so that they can become part of preserving culture and local wisdom.